Fixed bed column adsorption of sodium ion by zeolite synthesis from kaolin Malaysia: experiments and prediction via breakthrough curves - Norsuhailizah, Sazali; Zawati, Harun; Tijjani, Abdullahi; Noor Hasliza, Kamarudin; Norazlianie, Sazali; Mohd Riduan, Jamalludin; Siti Khadijah, Hubadillah (Springer International Publishing, 2022)
A continuous adsorption analysis was performed in a fixed-bed column to model the removal of sodium ions in seawater solution using the synthesized zeolite A (Na12Si12Al12O48(NaNO3)10(H2O) that was produced from Malaysian's kaolin. The effect of flow rate, influence concentration of sodium ions from seawater solution and zeolite bed height was investigated at a pH range of 6–8. The adsorption isotherm study by using the breakthrough curve analysis was used to model the removal process based on different flow rates, sodium ion concentration and bed height. Next, the kinetic model was used to illustrate the kinetic of particles' movement at different controlled parameters using Thomas, Adams–Bohart, and Yoon–Nelson. From the breakthrough curve analysis, the breakthrough capacity, qB (mg/g) result for flow rate (15.4, 10.64, and 7.7 mg/g) show decreases with increases in flow rate (5, 8, and 11 mL/min), respectively. The breakthrough capacity, qB (mg/g) for sodium ion concentration (15.4, 7.7, and 4.55 mg/g) decrease with decreases of sodium ion concentration (280, 140, and 70 mg/L) respectively. The breakthrough capacity, qB (mg/g) for bed height, increased (15.4, 18.67, and 36.4 mg/g) with increases in bed height (1, 1.5, and 2 cm), respectively. From the kinetic column result, the Adam Bohart model shows a better result compared to the Thomas model and Yoon and Nelson model based on the value of correlation coefficient (R2). The value of the correlation coefficient, R2 of Adam Bohart model, gives a higher value range of R2 (0.86–0.95) for flow rate, R2 (0.82–0.93) for bed height, and R2 (0.90–0.95) for ion concentration compared to the Thomas model with R2 range value 0.84–0.94 for flow rate, R2 (0.72–0.89) for bed height and R2 (0.78–0.88) for ion concentration and Yoon and Nelson model, R2 (0.84–0.94) for flow rate, R2 (0.69–0.89) for bed height and R2 (0.78–0.87) for ion concentration. The conducted analysis has shown that the column adsorption model of sodium ion adsorption by Zeolite-A was able to be expressed in Adam Bohart Model at the different flow rate, bed height and initial sodium ion concentration. The experimental results and model analysis showed that the synthesized zeolite A column can be used in desalination processes to extract sodium ions from seawater solution. The important purpose of eliminating the sodium ion in seawater is for drinking purposes.